Beyond Cost Savings: The Impact of Open Textbooks on Writing Studies Course Grades - LeMire, Sarah (Evidence Based Library and Information Practice, 2024)
Objective – This study was designed to explore the potential academic impact of open textbooks in writing courses.Methods – The researcher used statistical analyses of course outcomes for over 1,000 sections to examine the impact of OER usage on course GPA in three writing courses at an R1 university.Results – Study results reveal that using an OER textbook is associated with an overall increase in class GPA.Conclusion – When advocating for the use of OER in campus writing courses, librarians can point to findings that suggest improved student outcomes after a switch to OER in those courses.